BRIEF REMARKS ON THE IMPORTANCE OF THE MATERIAL OBJECT IN A CRIMINAL OFFENCE - Lamya-Diana HĂRĂTĂU; Ioan Mircea DAVID (Challenges of the Knowledge Society)
In preparing this particular research, we aimed to put under scrutiny the concept of the material object by analysing it in special given situations, in connection to the criminal offences that are most frequently encountered in practice, and thus to underscore the importance of this concept as a factor in the evolution of the legal framework. The challenges that appear to be inherent when categorising criminal offences into conduct crimes and result crimes do not constitute a novelty in the works of legal scholars, and even less so in practice, but in order to submit them to a proper analysis, it proves imperative that we possess a good grasp of the material object of the criminal offence, in order to establish the perpetrator”s level of criminal intent, as well as the manner in which criminal liability can be triggered.